2021
DOI: 10.3390/ijms22031238
|View full text |Cite
|
Sign up to set email alerts
|

Low Protein Expression of both ATRX and ZNRF3 as Novel Negative Prognostic Markers of Adult Adrenocortical Carcinoma

Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy that is associated with a dismal prognosis. Pan-genomic studies have demonstrated the involvement of ATRX and ZNRF3 genes in adrenocortical tumorigenesis. Our aims were to evaluate the protein expression of ATRX and ZNRF3 in a cohort of 82 adults with ACC and to establish their prognostic value. Two pathologists analyzed immuno-stained slides of a tissue microarray. The low protein expression of ATRX and ZNRF3 was associated with a decrease in overall surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 107 publications
(136 reference statements)
1
9
0
1
Order By: Relevance
“…Global loss of DAXX and/or ATRX expression (Fig. 35 ) may also be identified in ACCs, and this has shown to have prognostic value [ 18 , 120 , 136 ]. The application of MMR proteins (MLH1, MSH2, MSH6 and PMS2) has gained popularity not only for the purpose of screening for an extra-colonic manifestation of Lynch syndrome [ 18 , 179 , 180 ] (Fig.…”
Section: Question 10: Which Ancillary Tools Should Pathologists Consi...mentioning
confidence: 99%
“…Global loss of DAXX and/or ATRX expression (Fig. 35 ) may also be identified in ACCs, and this has shown to have prognostic value [ 18 , 120 , 136 ]. The application of MMR proteins (MLH1, MSH2, MSH6 and PMS2) has gained popularity not only for the purpose of screening for an extra-colonic manifestation of Lynch syndrome [ 18 , 179 , 180 ] (Fig.…”
Section: Question 10: Which Ancillary Tools Should Pathologists Consi...mentioning
confidence: 99%
“…In previous studies, several biomarkers associated with poor prognosis have been identified. Among them, eight potential biomarkers were selected from the GEPIA database: DLGAP5, SF1, NEK2, H2AX, PBK, PTEN, ATRX, and DAXX (34,39,(43)(44)(45)(46)(47). DLGAP5 has a unique function in stabilizing spindle formation, and it is strongly expressed during all phases of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sbiera et al proposed that SOAT1 may serve as molecular target of mitotane in ACC [ 9 ]. Accumulative literatures have demonstrated that inhibition of WNT–β-catenin signaling pathway [ 10 ], cell-cycle progression through down-regulation of p53–RB [ 11 ], defects in mismatch repair related enzymes (dMMR) [ 12 ], DNA methylation [ 13 ], and abnormal maintenance of telomere (ATRX [ 14 , 15 ], DAX [ 16 ] and TERT [ 8 , 17 ]), were closely bound up with the deterioration and poor prognosis of ACC. In addition, the unique feature of ACC is steroid differentiation, which has been viewed as a potential therapeutic target.…”
Section: Introductionmentioning
confidence: 99%